WELFARE AND SAFETY INDICATORS FOR WOMEN WASTE PICKERS IN RAJAPALYAM MUNICIPALITY - Ashifa, K.M.; Devi, M.Sharmila (International Journal of Research -GRANTHAALAYAH, 2017)
In India substantial people working in unorganized sectors as unorganized workers; transitional nature of the Indian economy, disparity in education, skill and training are some of the major factors abetting such a large concentration of workers in an area most vulnerable to exogenous economic vicissitudes. Women working in the unorganized sector deserve a separate mention as they are much marginalized (Khan, 2013). The present study is focused on women workers in unorganized sector especially the waste picking workers of Rajapalayam municipality. They are working in unprotected are in grave danger of contacting countless diseases through their daily and close contact with human waste. Some of these diseases, in addition to TB, include: campylobacter infection, cryptosporidiosis, giardiasis, and hand, and foot and mouth disease, hepatitis. According to Factories Act 1948 under section 21 to 50, the organization has to provide welfare and safety measures to protect its workers. The study tried to analyses the implementation of these welfare and safety measures among women pickers in study area. And it found that level of implementation of these measures is relatively poor. The study suggested to conduct weekly health check -up, recreation activities, counselling services, motivation trainings and awareness campaigns. Government intervention with the support of non- profit organization is to be very essential improve the quality of work life of women in unorganized sector, evidenced by the present study.